1990
DOI: 10.1128/jb.172.1.424-430.1990
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol facilitator of Escherichia coli: cloning of glpF and identification of the glpF product

Abstract: The glycerol facilitator is known as the only example of a transport protein that catalyzes facilitated diffusion across the Escherichia coli inner membrane. Here we show that the gene encoding the facilitator, glpF, is the first gene in an operon with glpK, encoding glycerol kinase, at 88 min of the E. coli chromosome. The operon is transcribed counterclockwise. We cloned the glpF gene, demonstrated that it complemented a chromosomal glycerol transport-minus mutation, and identified the gene product. The GlpF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
113
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(113 citation statements)
references
References 40 publications
0
113
0
Order By: Relevance
“…Sweet and coworkers (32) showed that GlpF is an aquaglyceroporin prototype in Escherichia coli (32). Aquaglyceroporins facilitate glycerol transport according to glycerol gradient.…”
Section: Discussionmentioning
confidence: 99%
“…Sweet and coworkers (32) showed that GlpF is an aquaglyceroporin prototype in Escherichia coli (32). Aquaglyceroporins facilitate glycerol transport according to glycerol gradient.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore GUP1 and GUP2 have recently been proposed to be involved in active transport of glycerol in yeasts (13). In contrast, the physiologically relevant role of GlpF from Escherichia coli, the closest bacterial homolog of Fps1p with 30.5% identity, is likely to be import of glycerol for catabolism (14,15).…”
Section: Major Intrinsic Protein (Mip)mentioning
confidence: 99%
“…The best-known example of this type of uniport is the glycerol facilitator (GlpF) of E. coli [29]. Glycerol uptake is followed by glycerol kinase catalyzed conversion to sn-glycerol 3-phosphate [30].…”
Section: Ii-b Electroneutral Solute Uniport (Fig 1-1)mentioning
confidence: 99%